Effect of mobile health intervention on perception and uptake of cervical cancer screening among nurses in Jos University Teaching Hospital - Olutomi Yewande Sodipo; Tolulope Olumide Afolaranmi; Hadiza Abigail Agbo; Ayuba Ibrahim Zoakah; Chikaike Ogbonna (Journal of Interventional Epidemiology and Public Health)
Introduction: Uptake of cervical cancer screening services among nurses in Nigeria has been documented as sub-optimal and perceptions have been linked to screening uptake. This study assessed the effect of a mobile health intervention on the perception and uptake of cervical cancer screening among nurses in Jos University Teaching Hospital.